2016
DOI: 10.1002/mren.201600047
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of Multi‐Block Polymer Synthesized in a Dual‐Catalyst Single CSTR

Abstract: This work aims at deriving analytical solutions for the molecular architecture of multi‐block polymer synthesized in a dual‐catalyst single CSTR. While the relevant equations are developed for homopolymerization, they can easily be extended to copolymerization. Special emphasis is placed on the quantities associated with each catalyst rather than the overall ones. However, if all rate parameters are available, the expressions can be used to calculate the properties of the material made by each catalyst as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Since the discovery of chain shuttling polymerization leading to the commercial production of diblock and multiblock polyolefin copolymers, , it has drawn a significant amount of research interest. Olefin block copolymers have unique and advantaged properties rendering them useful for a number of applications. For instance, ethylene/1-octene multiblock copolymers exhibit a unique balance of high melting point and flexibility compared to random copolymers with a similar comonomer content. While simple metal alkyls are the most commonly used chain shuttling agents, effort is being made to design and synthesize more sophisticated chain shuttling agents (CSAs), such as dual-headed CSAs (DHCSAs), to access novel polymer architectures, such as telechelic and triblock polymers. Bickelhaupt et al reported the synthesis of difunctional cyclic zinc compounds using Rieke zinc and dibromoalkane .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of chain shuttling polymerization leading to the commercial production of diblock and multiblock polyolefin copolymers, , it has drawn a significant amount of research interest. Olefin block copolymers have unique and advantaged properties rendering them useful for a number of applications. For instance, ethylene/1-octene multiblock copolymers exhibit a unique balance of high melting point and flexibility compared to random copolymers with a similar comonomer content. While simple metal alkyls are the most commonly used chain shuttling agents, effort is being made to design and synthesize more sophisticated chain shuttling agents (CSAs), such as dual-headed CSAs (DHCSAs), to access novel polymer architectures, such as telechelic and triblock polymers. Bickelhaupt et al reported the synthesis of difunctional cyclic zinc compounds using Rieke zinc and dibromoalkane .…”
Section: Introductionmentioning
confidence: 99%